Melt electrospinning of poly(lactic acid) and polycaprolactone microfibers by using a hand-operated Wimshurst generator. Issue 40 (30th September 2015) - Qin, Chong-Chong; Duan, Xiao-Peng; Wang, Le; Zhang, Li-Hua; Yu, Miao; Dong, Rui-Hua; Yan, Xu; He, Hong-Wei; Long, Yun-Ze
Abstract : A new melt electrospinning setup based on a small hand-operated Wimshurst generator with better portability and safety. Abstract : A conventional melt electrospinning setup usually needs a large, heavy high-voltage power supply and cannot work without a plug (electricity supply). In this article, we report a new melt electrospinning setup based on a small hand-operated Wimshurst generator, which can avoid electrical interference between the high-voltage spinning system and the heating system, and make the setup very portable and safe. Poly(lactic acid) (PLA) and polycaprolactone (PCL) fibers with diameters of 15–45 μm were fabricated successfully by using this apparatus. Experimental parameters such as the rotational speed of the generator handle (a half turn to two turns per second) and the spinning distance (2–14 cm) were investigated. In addition, PLA and PCL fibers were directly melt-electrospun onto a pork liver, and the temperature and adhesiveness of the deposited fibers were studied. The results indicate that the apparatus and melt-electrospun polymer microfibers may be used in dressing for wound healing.